To expand the expression \((2x + 5)(2x^2 + x - 3)\), we will use the distributive property (also known as the FOIL method for binomials).
-
Distribute \(2x\) to each term in the second polynomial: \[ 2x \cdot 2x^2 = 4x^3 \] \[ 2x \cdot x = 2x^2 \] \[ 2x \cdot (-3) = -6x \]
-
Now distribute \(5\) to each term in the second polynomial: \[ 5 \cdot 2x^2 = 10x^2 \] \[ 5 \cdot x = 5x \] \[ 5 \cdot (-3) = -15 \]
-
Now combine all these results: \[ 4x^3 + 2x^2 - 6x + 10x^2 + 5x - 15 \]
-
Combine like terms:
- For \(x^2\): \(2x^2 + 10x^2 = 12x^2\)
- For \(x\): \(-6x + 5x = -x\)
-
So we can now write the polynomial in standard form, combining all the like terms: \[ 4x^3 + 12x^2 - x - 15 \]
Thus, the expanded polynomial in standard form is: \[ \boxed{4x^3 + 12x^2 - x - 15} \]